Effect of polystyrene nanoplastics exposure on gene expression and pathogenesis of zoonotic pathogen, Edwardsiella piscicida - Ju Bin Yoon; Yongjoon Yoon; Jeong Woo Park; Aaron M. Yerke; Yogini S. Jaiswal; Leonard L. Williams; Sungmin Hwang; Ki Hwan Moon (Ecotoxicology and Environmental Safety, 2024)
A surge in the number of anthropogenic pollutants has been caused by increasing industrial activities. Nanoplastics are spotlighted as a new aquatic pollutant that are a threat to microbes and larger organisms. Our previous study showed that the subinhibitory concentrations of aquatic pollutants such as phenol and formalin act as signaling molecules and modulate global gene expression and metabolism. In this study, we aimed to investigate the impact of a new type of anthropogenic contaminant, polystyrene (PS) nanoplastics, on the expression of key virulence factors in zoonotic pathogen Edwardsiella piscicida and the assessment of potential changes in the susceptibility of zebrafish as a model host. The TEM data indicated a noticeable change in the cell membrane indicating that PS particles were possibly entering the bacterial cells. Transcriptome analyses performed to identify the differentially expressed genes upon PS exposure revealed that the genes involved in major virulence factor type VI secretion system (T6SS) were down-regulated. However, the expression of T6SS-related genes was recovered from the PS adapted E. piscicida when nanoplastics are free. This demonstrated the hypervirulence of pathogen in infection assays with both cell lines and in vivo zebrafish model. Therefore, this study provides experimental evidence elucidating the direct regulatory impact of nanoplastics influx into aquatic ecosystems on fish pathogenic bacteria, notably influencing the expression of virulence factors.